PENGARUH SUBSTITUSI TEPUNG PISANG “ROA” (Musa acuminate) TERHADAP TINGKAT KESUKAAN BISKUIT - Lateka, Fritsman H.; Lalujan, Lana E.; Taroreh, Mercy I. R. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2021)
The aim of this research was to determine the formulation of banana flour